Understanding of Professional Sckeptis: Are The Sequence of Evidence and Critical Thinking Determining Factors? (Experimental Research) - Apandi, R Nelly Nur; Sofia, Alfira; Zulhaimi, Hanifa (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
Understanding professional skepticism will help the auditor to assess the risks of material misstatement in the financial statements appropriately. One of the efforts lecturers can make to improve this understanding is through an audit learning model that links efforts to collect and evaluate audit evidence into question exercises. This study aims to see audit learning regarding evidence collection (sequence of evidence) and evidence assessment (critical thinking about mitigation risk) can influence students' understanding of skepticism. The research was conducted on 120 students of the UPI accounting study program class of 2017 and 2018. The research method was carried out by experiment. The research design in this study used a 2x2 factorial design. The study results prove that learning about evidence collection (sequence of evidence) and assessment of evidence (critical thinking about mitigation risk) increases understanding of professional skepticism. The study results have implications for the development of audit learning methods that emphasize critical thinking efforts about risk mitigation that can increase students' understanding of professional skepticism.